Biological Preoxidation Of A Pyrite Gold Concentrate - Richard W. Lawrence; J. David Gunn (Society for Mining, Metallurgy & Exploration, 1985)
Gold and silver often occur finely disseminated in sulphide minerals such as pyrite. The use of biological leaching to dissolve pyrite and liberate gold has been extensively studied for a concentrate from the Porgera deposit, Papua New Guinea. The successful operation of a continuous bioleach circuit has been demonstrated. Bioleach residues were cyanide leached to extract gold and silver, and unreacted pyrite recovered for recycle to the bioleach. A 26 day steady state continuous bioleach test on a concentrate assaying 14.3 g/tonne Au and 87.0 g/tonne Ag produced residues with an average 73.5% weight loss and a pyrite oxidation of 88%. Cyanidation and recovery of pyrite from the cyanide residues for recycle gave overall recoveries of 92.1% gold and 74.6% silver. A proportion of the remaining precious metals was found in the bioleach solutions and may be recoverable. Losses to tails were 3.0% gold and 8.1% silver. Final tails represented 14.3% of the feed weight and averaged 1.84 g/tonne Au. A description of the continuous bioleach circuit and bioleach residue handling procedures, and the results of the study are presented. The features and advantages of biological oxidation as a pretreatment for refractory precious metal ores and concentrates are discussed.